40th Winter School on Vibroacoustical Hazards Suppressions Szczyrk, Poland, February 27 –March 2, 2012 - BUKOWSKI, Roman (Archives of Acoustics, 2012)
Traditionally you are invited to acquaint yourselveswith some abstracts of lectures submitted to the 40thWinter School on Vibroacoustical Hazards Suppres-sions. This national School is traditionally held at theturn of February and March and is organized in differ-ent places of Silesian Beskidy Mountains. This year itis again held in Szczyrk.This year we celebrate the jubilee edition of theSchool. Because of this anniversary the conferenceapart from standard organizers, i.e. Upper Silesian Di-vision of the Polish Acoustical Society and Instituteof Physics – Science-Didactic Center at the SilesianUniversity of Technology, has also a co-organizer – theCommittee on Acoustics of the Polish Academy of Sci-ences. Moreover there are two splendid honorary pa-trons – Prof. Zbigniew Engel, president of the Com-mittee on Acoustics of the Polish Academy of Sciences,and Prof. Andrzej Bluszcz, director of the Institute ofPhysics – Science-Didactic Center at the Silesian Uni-versity of Technology.The conference is a forum for all environmen-tal vibroacoustic fields. Particularly it concerns traf-fic noise, industry noise, vibroacoustics of machines,room acoustics, noise protection and similar problems.Works which are presented during the School are the-oretical, experimental, measuring, technical, appliedand normative. The program of the 40th edition ofthe School is very rich – there are some occasional lec-tures to celebrate our anniversary and many plenarylectures which recapitulate different achievements inPolish environmental acoustics. It should be mentionedthat this year Polish acousticians celebrate the cen-tennial birthday of a famous Polish scientist, IgnacyMalecki.The School lectures and other conference materialswill be published in the “Materials of the XL WinterSchool on Vibroacoustical Hazards Suppressions” (inPolish) edited by dr. Roman Bukowski. This publica-tion will be intended for participants of the School andfor many libraries in Poland.